Penyembahan Sejati Dalam Yohanes 12:1–8: Studi Eksegetis Dan Kontekstual Pada Gereja Pentakosta Indonesia Sidang Lippo Cikarang: True worship in John 12:1–8: Exegetical and Contextual Studies At the Indonesian Pentecostal Church Lippo Cikarang Congregation - Elia Siregar; Brigjen Silaen; Duma Uli Manurung (MURAI: Jurnal Papua Teologi Konstekstual, 2026)
Worship in many churches is frequently understood as a liturgical activity centered on music and ritual, while its theological meaning as a life response to Christ often receives less attention. This study aims to examine the meaning of worship in John 12:1–8 and analyze its actualization in the Indonesian Pentecostal Church (Gereja Pentakosta Indonesia) Lippo Cikarang Congregation. The study employed a qualitative approach using narrative exegesis of John 12:1–8 integrated with a practical theological perspective. Data were collected through library research on biblical and theological sources, complemented by observation and documentation of worship practices in the congregation. Data were analyzed through data reduction, data display, theological interpretation, and conclusion drawing. The findings reveal that true worship in John 12:1–8 is a faithful response to God's grace expressed through love, sacrifice, humility, and complete devotion to Christ. The study identifies five theological principles of worship: worship as a response to divine grace, worship involving sacrifice, worship rooted in love for Christ, worship manifested in humility, and worship producing a transformative witness within the community. Furthermore, the findings demonstrate that the worship practices of the Indonesian Pentecostal Church Lippo Cikarang Congregation actualize these principles through the integration of liturgical worship and diaconal ministry. This study contributes to the development of worship theology by integrating exegetical analysis with practical theology in the context of contemporary Pentecostal ministry.